A review of the parametric characteristics of urban environment and it's influence to the urban quality of life - Eusuf, Muhammad Abu; R. Sabeek Eusuf, Muhammad Saadmann; Rahman Sami Eusuf, Muhammad Mehbub; Ibrahim, Mansor (e-IPH e- International Publishing House Ltd. United Kingdom, 2018)
This study covers the influence of the parameters and factors that modify the urban inhabitants’ quality of life. Recently, professionals paid attention in and concern for environmental effects to the cycle of urban fabrics and structural health. The parametric matrix confronted by urbanization growth and affects the daily routine of urban dwellers. Then the purpose is to investigate the parametric characteristics of the urban environment at scale and which needs to be validated by experiments and observation. A valid model in neighbourhood scale has been employed for the data analysis. Results displayed environmental modification in micro level and enormous macro-level.